2014
DOI: 10.1111/een.12173
|View full text |Cite
|
Sign up to set email alerts
|

Life stage‐dependent effects of experimental heat waves on an insect herbivore

Abstract: 1. Worldwide concern about the consequences of climate change has prompted efforts to understand and predict the responses of populations to changes in temperature.2. A heat wave can adversely affect organisms, may affect different life stages differently, and could decrease populations. In this study, green peach aphid [Myzus persicae (Sulzer)] nymphs, reproductive adults, and late-reproductive adults were exposed to a heat wave, defined as 5 ∘ C above the control temperature regime for five consecutive days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
1
20
0
2
Order By: Relevance
“…MRR and SIT) or decreased differences in fitness using refined transgenesis under current and future climate conditions. As a direct measure of Darwinian fitness (Demetrius & Ziehe, 2007), the intrinsic rate of population growth has been used to compare growth differences in populations under various environmental conditions (Davis, Radcliffe, & Ragsdale, 2006;Kuo, Lu, Chiu, Kuo, & Hwang, 2006;Lu & Kuo, 2008 (Chiu et al, 2015;Hazell et al, 2010;Kuo, Chiu, & Perng, 2006). Our study confirmed the significant effects of temperature on these life-history traits and indicated that the optimal temperature of wild and transgenic B. dorsalis existed at and below our experimental warming range, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…MRR and SIT) or decreased differences in fitness using refined transgenesis under current and future climate conditions. As a direct measure of Darwinian fitness (Demetrius & Ziehe, 2007), the intrinsic rate of population growth has been used to compare growth differences in populations under various environmental conditions (Davis, Radcliffe, & Ragsdale, 2006;Kuo, Lu, Chiu, Kuo, & Hwang, 2006;Lu & Kuo, 2008 (Chiu et al, 2015;Hazell et al, 2010;Kuo, Chiu, & Perng, 2006). Our study confirmed the significant effects of temperature on these life-history traits and indicated that the optimal temperature of wild and transgenic B. dorsalis existed at and below our experimental warming range, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…We suspect that these differences, amounting to nearly 4 °C in total, are ecologically highly relevant. Still too often, our view on insect life histories is dominated by a single stage, mainly the adult one, only (Kingsolver, ; Kingsolver et al ., ; Radchuk et al ., ; Chiu et al ., ). Our data clearly indicate that eggs and hatchlings are very sensitive to heat while others such as pupae are less susceptible.…”
Section: Discussionmentioning
confidence: 97%
“…A potentially crucial aspect of thermal biology has hitherto received surprisingly little attention, namely variation in thermal limits throughout ontogeny (Bowler & Terblanche, 2008;Kingsolver et al, 2011;Chiu et al, 2015;Pincebourde & Casas, 2015). In particular, in arthropods, our view on organismal biology is still too often focussed on the typically more conspicuous adult stage (Kingsolver, 2009;Kingsolver et al, 2011;Radchuk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies on the impact of heat stress on pest insects are scarce. Published research testing the response of insects to extreme heat kept the experimental temperature or humidity constant with a variable duration or repeated the identical peak pattern several times (Kimura, ; Davis et al ., ; Piyaphongkul et al ., ; Chen et al ., ; Sentis et al ., ; Chiu et al ., ).…”
Section: Discussionmentioning
confidence: 97%